KONSEP SYARAT SAH AKAD DALAM HUKUM ISLAM DAN SYARAT SAH PERJANJIAN DALAM PASAL 1320 KUH PERDATA - Muhammad Romli (TAHKIM, 2022)
Community social activities will not be separated from the name of the transaction, be it in barter, renting or buying and selling. The activity will be due to how the community can fulfill its basic needs, so that the transaction cannot be abandoned. However, people sometimes do not think about all the transaction activities are legal or not, because they are more focused on their needs. In addition, economic activities and systems are increasingly developing, as is the case with Islamic economics, this has an impact on the regulation required as a formal legal for every transaction made. But not all of these regulations exist to encourage the development of the Islamic economic system.Because there must be a solution to make certain legal regulations, to make a belief that the transactions carried out by the community are legal both Islamic and positive law, thus having strong legal force. In this paper, we try to analyze the concept of contract in muamalah fiqh and the concept of agreement in the Civil Code. The focus of the questions in this research is. What is meant by the contract and the legal basis of the contract, how is the difference between Ulama and the concept of the contract, how is the comparison of the concept of the contract in the Fiqh of Muamalah with the concept of agreement in the Civil Code.This paper is compiled based on a comparative method, which is trying to compare an Islamic law with a statutory regulation in the matter of the legality of a contract. The conclusions in this paper are. In terms of Article 1320 of the Civil Code regarding the legal requirements of an agreement or contract with the legal terms of the contract in muamalah fiqh there is not so much difference, even the authors are of the same opinion. However, the difference is about the legal source of the contract taken, because it is in fiqh muamalah the legal basis in the act is Q.S al-Maidah paragraph 01. But in the Civil Code the legal basis for making an agreement is from article 1338 concerning the principle of freedom to make an agreement Keywords: Agreement Terms, Islamic Law, Article 1320 Civil Code.